2019
DOI: 10.1038/s41467-019-13537-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonmagnetic single-molecule spin-filter based on quantum interference

Abstract: Key spin transport phenomena, including magnetoresistance and spin transfer torque, cannot be activated without spin-polarized currents, in which one electron spin is dominant. At the nanoscale, the relevant length-scale for modern spintronics, spin current generation is rather limited due to unwanted contributions from poorly spin-polarized frontier states in ferromagnetic electrodes, or too short length-scales for efficient spin splitting by spin-orbit interaction and magnetic fields. Here, we show that spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 41 publications
5
65
1
Order By: Relevance
“…Therefore, molecular orbitals are expected to preserve their symmetry and localized nature. In the collinear magnetic case without SOC, it has been shown that a nonmagnetic organic molecule can act as a "halfmetallic" conductor due to either orbital symmetry arguments [27,28] or quantum interference effects [29,30], leading to nearly fully spin-polarized conduction. In addition, a nearly perfect spin filtering was reported when a vanadium-benzene wire is placed between two magnetic electrodes [31].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, molecular orbitals are expected to preserve their symmetry and localized nature. In the collinear magnetic case without SOC, it has been shown that a nonmagnetic organic molecule can act as a "halfmetallic" conductor due to either orbital symmetry arguments [27,28] or quantum interference effects [29,30], leading to nearly fully spin-polarized conduction. In addition, a nearly perfect spin filtering was reported when a vanadium-benzene wire is placed between two magnetic electrodes [31].…”
Section: Introductionmentioning
confidence: 99%
“…23,24 But only few reports have described QI effects in systems exhibiting spin polarization. [25][26][27] Recently, Li et al proposed a mechanism for tuning the spin filtering ratio based on QI effects in a nickel based junction. 28 Ratner and coworkers have demonstrated that how DQI features can be controlled by addition of a donor or acceptor group to the polyacetylene chain bridging graphene nanoribbons (ZGNR).…”
Section: Graphical Toc Entrymentioning
confidence: 99%
“…24,25 But only few reports have described QI effects in systems exhibiting spin polarization. [26][27][28][29] Recently, Li et al proposed a mechanism for tuning the spin filtering ratio based on QI effects in a nickel based junction. 30 Ratner and coworkers have demonstrated that how DQI features can be controlled by addition of a donor or acceptor group to the polyacetylene chain bridging graphene nanoribbons (ZGNR).…”
Section: Introductionmentioning
confidence: 99%